Application of Relief-Point Brile Font in the System of Ornamental Decoration - I. Bratisheva, Yu.; A. Zyabneva, O.; A.Oranskaya, I. (International Journal of Engineering and Technology, 2018)
The present article addresses the issue of psychological adaptation of environment for people with disabilities. The use of braille boldface as an ornamental design of environmental objects, which facilitates the exchange of information between people with different capabilities and the creation of emotional comfort for each person, is proposed.Â